Visual Cryptography with RSA Algorithm for Color Image - ., Ratnadewi; Santoso Sugiharto, Benny; Kurniasih, Nuning; Abdullah, Dahlan; Bagus Ary Indra Iswara, Ida; Napitupulu, Darmawan; Laritmas, Selfianus; Mouw, Erland; Saleh Ahmar, Ansari; Kurniawati, Nanik; Rahim, Robbi (International Journal of Engineering and Technology, 2018)
RSA algorithm founded by Rivest, Shamir and Adleman is an algorithm that based on the use of factorization of a significant number to its factor, and the element must be the prime number. Factorization used to find the private key. In this paper, the RSA algorithm will be used in a visual cryptographic to encrypt and decrypt a color image. The test will conduct with five different photos. Assessment performed using Structural similarity (SSIM) to compare the matrix value of the initial image with the decrypted image. SSIM generates a value of 1 on all pictures. The proves that the Matrix Value in the initial and after decoded images has the same amount. The image decryption will worsen; can be seen from the smaller SSIM value.Â Â Â